ANALYSIS OF ARABIC TRANSLATION DIGITAL DICTIONARY APPLICATIONS IN THE ERA OF SOCIETY 5.0 - Aprilia, Risda; Massofia, Fitrah Dinanti; Hasaniyah, Nur (Lugawiyyat, 2024)
Translation is needed as a tool to make it easier to understand a language called a dictionary. At present we can find that dictionaries are not only in printed form, but along with the sophistication of technology, digital dictionary innovations have emerged. The digital dictionary plays an important role in the process of someone understanding a language from its speakers, and as a technological tool in the form of an application and has many roles in the learning process. This research is included in descriptive research with a qualitative approach, and using library research techniques is the step of the researcher in collecting data on the digital Arabic dictionary application. While data analysis is a narrative study on "digital dictionary applications". The results of this study indicate that the problem of the accuracy of truth in electronic dictionaries in Arabic must be a common concern because dictionaries are positioned as learning resources and references for students. The digital dictionary plays an important role in a person's process of understanding a language from its speakers, and as a technological tool. The Arabic translation method consists of a word-by-word translation method, a literal translation method, and a Tasharruf translation method. Students also look for and match the meaning of Arabic words to Indonesian in a good and easy-to-understand arrangement.